Analisis Kekuatan Tarik Dan Struktur Mikro Pada Sambungan T-Joint Dan Butt Joint Pipa Alumunium Dengan Metode Soldering - Martanto, Prihatin Iwan; , Agus Dwi Anggono, ST, M.Eng, Ph.D (2017)
Soldering method have been used to joint aluminium pipe to increase the efectiveness and eficiency in the product creation due to aluminiun was a hard-to weld material. This research objective is to joint aluminium pipe of 16 mm diameters and 1 mm thickness by using soldering method with alusol filler. Joinning strength of soldering will be investigated as well. There are two types of joinning i.e butt joint and T-joint. Analysis was conducted by using tensile test and photo micro to investigate the material structure. Tensile test standard was adopted ASTM E8M and ASTM E3 for photo micro. The soldering result shows the breaking area of soldering zone. The tensile test of T-joint was given the tensile value of 10.959 N/mm2 and the strain walue was 3.93%. Tensile test of butt joint was delivered stress of 3.124 N/mm2 and strain of 3.9%. The micro structure of HAZ was shown smaller grain due to the heat effect to the aluminium, and also in the soldering zone of filler material. It was seen smaller grain size compare to the base aluminium